OP0042 Clinical and Radiographic Outcomes at Two Years and the Effect of Tocilizumab (TCZ) Discontinuation Following Sustained Remission in the Second Year of the Act-Ray Study. (23rd January 2014) - Huizinga, T. W. J.; Donka, T.; Conaghan, P. G.; Martin-Mola, E.; Schett, G.; Amital, H.; Xavier, R. M.; Troum, O.; Bernasconi, C.; Dougados, M.
Abstract : Background: In ACT-RAY, MTX-IR patients (pts) with moderate to severe RA were randomized to either the add-on (TCZ+MTX) or the switch (TCZ+placebo [PBO]) strategy arm. 24- and 52-week data demonstrated clinical and radiographic benefit without clinically meaningful differences between the 2 arms for most endpoints. During year 2, the protocol included a step-down strategy with the goal of achieving drug free remission (discontinuation of study drugs while DAS28 remained <2.6). Objectives: To assess 1) efficacy and safety of TCZ-based treatment strategies and 2) ability to discontinue study drugs in year 2 after having achieved sustained clinical remission. Methods: ACT-RAY is a phase 3b trial. Pts were randomized to either add TCZ 8 mg/kg IV every 4 weeks (q4w) to their existing MTX (add-on) or to switch to TCZ 8 mg/kg IV q4w with oral PBO (switch). Using a treat to target (T2T) approach, OL DMARDs other than MTX were added from week 24 usually if DAS28 was >3.2, while maintaining blinding of MTX/PBO. In year 2, if sustained remission was achieved (defined as DAS28<2.6 at 2 consecutive visits 12 weeks apart), first TCZ and then OL DMARDs and MTX/PBO were discontinued. In case of flare, the last effective treatment or TCZ with blinded MTX/PBO was restarted. Results: 76% of 556 randomized pts (mean disease duration 8.2 y, baseline DAS28 6.4, annualized Genant-Sharp Score (GSS) progression 9.5) completed year 2. Withdrawal reasons included lack of efficacy (1.8% add-on, 4.7% switch) and adverse events (AEs; 9.7% add-on, 11.2% switch, including 3 and 6 deaths, respectively). About 50% of pts entering into year 2 discontinued TCZ after achieving the protocol-defined sustained remission criteria and 86% of these pts experienced flare before the end of year 2 (study is ongoing, final estimates will be available at year 3). The table shows key efficacy results. Despite many pts stopping TCZ for some period, radiographic progression was minimal in both arms. Safety results were consistent with previous findings. SAEs and serious infections per 100 PY were 11.9 and 4.2, respectively, for the add-on and 14.6 and 3.8, respectively, for the switch arm. In pts with normal baseline values, ALT elevations >3x ULN were observed in 13.5% of add-on and 4.9% of switch pts. Image/graph: Conclusions: Previous clinical improvements were largely maintained in year 2 of the ACT-RAY study. Year 2 results suggest that T2T strategies can be successfully utilized in MTX-IR pts (whether or not currently on MTX) to achieve sustained remission. However, stopping TCZ in this established RA pt population was associated with a high flare risk. Disclosure of Interest: T. J. Huizinga Consultant for: Abbott, Axis Shield Diagnostics, Biotest AG, BMS, Crescendo Bioscience, Roche, Novartis, Schering-Plough, UCB, Wyeth, Pfizer, T. Donka Employee of: F. Hoffmann-La Roche Ltd, P. Conaghan Speakers bureau: BMS, Janssen, Pfizer and Roche, E. Martin-Mola: None Declared, G. Schett: None Declared, H. Amital: None Declared, R. Xavier Consultant for: Pfizer, Roche and Merck, O. Troum Grant/research support from: ACT-RAY clinical trial, Speakers bureau: Roche/Genentech, C. Bernasconi Employee of: F. Hoffmann-La Roche Ltd, M. Dougados Consultant for: Pfizer, Roche, Abbott, UCB